Bibliographical summary of researches carried out on the recycling and recovery of waste from mining for high-performance concrete production - Gouasmi Meriem; Babouri Laidi (University Of Eloued جامعة الوادي, 2020)
The exhaustion of natural deposits of aggregates and the difficulties in opening new quarries requires the search for new sources of supply. For this, the recycling and recovery of waste is today considered a solution in order to meet the deficit in terms of production on the one hand and environmental protection . The overall objective of this paper is to reviews studies on the use of natural waste as an additional material in the further development of various recycled concretes., Such as marble powder (MP), metakaolin (MK), to discuss the effects of each waste on compressive strength, sorptivity, permeability, water absorption, chloride penetration, corrosion resistance, then assess which of these wastes is a better replacement for cement in concrete.
Intervention
Keywords: waste; mine and quarry; environment; recycling; Concrete; physical and mechanical characteristic